Validation of the Indonesian version of the graded chronic pain scale 2.0 in pain-related temporomandibular disorders (Medical Journal of Indonesia, 2020)
BACKGROUND Pain associated with oral problems is one of the most frequent chronic pain of temporomandibular disorders (TMDs). This study was conducted to analyze the psychometric properties of the Indonesian version of the graded chronic pain scale 2.0 (GCPS-ID) in Indonesian patients with TMDs. METHODS The English version of the GCPS version 2.0 was translated and back-translated according to international guidelines. This study conducted from June to December 2016 at the Dental Hospital, Faculty of Dentistry, Universitas Indonesia, and the participants were 202 TMDs patients who had never undergone temporomandibular joint surgery or suffered facial pain for more than 6 months. The evaluation of the GCPS-ID included the internal consistency test, test-retest reliability, and construct validity tests. RESULTS The GCPS-ID had a high internal consistency (Cronbach’s alpha = 0.896). The intraclass correlation coefficient of the pain intensity and the disability score were 0.789 and 0.706, respectively. The convergent validity demonstrated a moderately positive correlation between the GCPS-ID and the Indonesian version of oral health impact profile for TMD for pain (r = 0.595; p<0.001) and disability (r = 0.488; p<0.001). The discriminant validity between GCPS-ID and the subjective patient’s quality of life revealed a weak positive correlation (r = 0.195; p = 0.191). CONCLUSIONS GCPS-ID is a reliable and valid assessment tool for evaluating TMD pain in Indonesia.